Questioning the Terms: â€œRegular and Irregular Verbsâ€ in English - Arief, Yusuf Al (Master Program in Linguistics, Diponegoro University, 2016)
English verbs have unique inflectional markers which show the past tense. There are two inflectional markers that become the categorization of these verbs. The first marker is the additional morpheme [d] or [ed]. All verbs with this marker are categorized as regular verbs. The second marker is the verb morphophonemic change like the word â€˜singâ€™ [+present] and â€˜sangâ€™ [+past]. The verbs of this kind are categorized as irregularâ€™ verbs. Simply, the regular verbs are those whose changes can be morphophonemically predicted while irregular verbs are the ones whose changes are morphophonemically unpredictable. This research is aimed to figure out whether there are morphophonemic inflectional patterns for irregular verbs. This paper is descriptive qualitative research. The data were collected using observation with note taking technique. I analyzed the data using distributional method. The result of the analysis shows that there are four additional sounds added to the â€™regularâ€™ verbs such as [d], [t], [Éªd], and [É™d]. I also found that the morphophonemic changes in the irregular verbs are influenced by the syllable number, the positions, and the environments of the peak sounds. These findings prove that the term â€œirregular and regularâ€ is not fully appropriate to classify the verbs.